The moderating effect of gender between customer quality factors and loyalty toward internet service provider in Malaysia / Muhammad Shafiq Harun - Harun, Muhammad Shafiq (Bachelor of Science (Hons.) Statistics, 2015)
Customer’s quality based on commitment, trust, and satisfaction theory can explain and predict the success of a relationship between an internet service provider in Malaysia and its customers, measured in terms of loyalty. This study proposed a model to express the relationship and included gender as a moderator in the relationship. This study also developed a questionnaire to test the structural model and used a sample in Malaysia to check its validity and reliability. Analysis provided strong support for our hypotheses that gender exerted a significant moderating role on our model relationships. The influence of loyalty on commitment, trust and satisfaction was significantly for moderating effect of gender